Multisite Evaluation of Toothbrushes and Microbial Growth in the Hospital Setting. Issue 2 (March 2023) - DeJuilio, Patti; Powers, Jan; Soltis, Lisa M.; Brooks, Jo Ann
Abstract : Design: This observational, descriptive study was conducted to determine the prevalence of microbial growth on toothbrushes found in hospital patient rooms. Methods: Toothbrush sampling was conducted in 136 acute care hospitals and medical centers from November 2018 through February 2022. Inclusion criteria for the units and patient rooms sampled were as follows: general adult medical-surgical units or critical care units; rooms occupied by adults 18 years or older who were capable of (1) mobilizing to the bathroom; (2) using a standard manual, bristled toothbrush; and (3) room did not have signage indicating isolation procedures. Results: A total of 5340 patient rooms were surveyed. Of the rooms included, 46% (2455) of patients did not have a toothbrush available or had not used a toothbrush (still in package and/or toothpaste not opened). Of the used toothbrushes collected (n = 1817): 48% (872/1817) had at least 1 organism; 14% (251/1817) of the toothbrushes were positive for 3 or more organisms. Conclusions: These results identify the lack of availability of toothbrushes for patients and support the need for hospitals to incorporate a rigorous, consistent, and comprehensive oral care program to address the evident risk of microbe exposure in the oral cavity.